Sources of knowledge and trust in authorities as prerequisites of pre-service teachers' reflective judgment skills in the context of socioscientific issues - Dilek Karışan; Ingo Eilks (Journal of Pedagogical Research, 2023)
Developments in science and technology enrich life in the 21st century. To cope with life in society, reflective judgment and decision-making abilities on both the individual and societal levels are needed. Schools must prepare the younger generations to become responsible citizens who are able to make reflective judgments. This study elaborates on how pre-service teachers in Türkiye make reflective judgments as persons who will go on to teach secondary school-level students in the future. The study focuses on sources of information students use, their trust in expert knowledge, and levels of reflective judgment skills. The study is based on a qualitative approach combining analyses of recordings of classroom discussions and interviews. The study found different levels of reflective judgment skills among the students and identified the sources of knowledge they select to make judgments and measured their trust in expert knowledge.  The more students trust expert knowledge, the more reflective they are toward developments in science and technology.